Critical Role of Ser-520 Phosphorylation for Membrane Recruitment and Activation of the ZAP-70 Tyrosine Kinase in T Cells - Yang, Yaoming (American Society for Microbiology, 2003)
Regulation of protein tyrosine kinases (PTKs) by tyrosine phosphorylation is well recognized; in fact, nearly all PTKs require phosphorylation of tyrosine residues in their “activation loop” for catalytic activity. In contrast, the phosphorylation of PTKs on serine and threonine residues has not been studied nearly as much. We report that the ZAP-70 PTK contains predominately phosphoserine in normal T lymphocytes as well as in Jurkat T leukemia cells. We have identified one site of phosphorylation as Ser-520 and find this site to be important for the recruitment and activation of ZAP-70 in T cells. Mutant ZAP-70-S520A had reduced ability to autophosphorylate and to mediate antigen receptor-induced interleukin 2 gene activation and was not enriched at the plasma membrane. These defects were rescued by addition of a myristylation signal to the N terminus of ZAP-70-S520A to force its plasma membrane and lipid raft localization. We conclude that phosphorylation of ZAP-70 at Ser-520 plays an important role in the correct localization of ZAP-70 and in priming ZAP-70 for its acute recruitment and activation upon antigen receptor ligation.